Case Report: Positive Pressure Therapy Combined With Endolymphatic sac Surgery in a Patient With Ménière's Disease - Fukushima, Munehisa; Akahani, Shiro; Inohara, Hidenori; Takeda, Noriaki (Frontiers in Surgery, 2021)
Positive pressure therapy (PPT) is applied for medically-intractable vertigo in Ménière’s disease (MD); however, it remains unknown whether PPT affects in vivo endolymphatic hydrops (EH). In this study, we describe a 5-year course of MD in a patient in which EH was repeatedly observed. As the patient experienced recurrent vertigo attacks after endolymphatic sac surgery, he began to use the PPT device additionally and vertiginous episodes decreased in accordance with a decrease in the EH volume. PPT, if combined with surgery, might be more effective compared with surgery alone.